Макромоделювання стадії метаногенезу зброджування твердих побутових органічних відходів у біогазових установках - Гураль, Ірина Володимирівна (НТУ "ХПІ", 2016)
Розглянуто задачу моделювання процесів анаеробного мікробіологічного бродіння на стадії метаногенезу з дотриманням балансу. Запропоновано та обґрунтовано модель на цій стадії будувати у вигляді інтервальної дискретної динамічної моделі. Обґрунтовано метод структурної ідентифікації інтервальної дискретної динамічної моделі на принципах функціонування бджолиної колонії у процесі пошуку їжі, який забезпечує можливість отримання простіших структур моделі із заданими прогностичними властивостями по відношенню до існуючих методів.

The problem of modeling the processes of anaerobic microbiological fermentation on the methanogenesis stage with keeping the balance is considered in this work. It is proposed and justified to build the model on this stage in the form of an interval discrete dynamic model. The method of structural identification of the interval discrete dynamic model based on the principles of functioning of a honey bee colony in the food search process, which provides the possibility of obtaining simple model structures with specified prognostic properties relative to existing methods, is justified. A macromodel of the fermentation process on the methanogenesis stages based on the interval discrete dynamic model, which provides guaranteed prognostic properties for different anaerobic microbial fermentation under changing acidity, is developed in this paper. It is shown that the resulting model describes adequately and qualitatively the percentage of SSU rRNA methane forming bacteria at biogas plants
Macromodelling of methanogenesis stage of municipal solid organic waste fermentation at biogas plants
Keywords: екологічні проблеми; структурна ідентифікація; дискретна динамічна модель; алгоритм бджолиної колонії; анаеробне мікробіологічне бродіння; structure identification; biogas plants; methanogenesis; interval discrete dynamic model